ニシ オングルトウ オヨビ テオイヤトウ ノ ショクセイ ブンプ ト カンキョウ ヨウイン - 清水, 寛厚; シミズ, ヒロアツ; Shimizu, Hiroatsu (国立極地研究所, 1977)
P(論文) 1)西オングル島とテオイヤ島の那須・地衣類群落の分布およびその生育に関与する環境要因について調査を行った.2)オオハリガネゴケとムラサキヤネゴケの2種により構成される蘚類群落は,西オングル島で約300の分布地点が確認され,テオイヤ島ではわずか2地点であった.岩石着生地衣群落は,西オングル島にのみ7分布地点であり,いずれも鳥との関連が強くみられた.3)西オングル島の蘚類分布は島西部に集中偏在するが,その原因について考察した.4)蘚類群落の生育地を地形-ドリフトの条件に着目して分けると四つのタイプに区分された.両島を通じてStand type II (西斜面に形成されたドリフト横)の群落が顕著である.5)蘚類群落の大部分は西寄り斜面に発達する.この原因について,西寄り斜面はドリフトの日射による融雪水が,蘚類の生育期間中連続的に供給されることによると考察した. The vegitational distributions and habitats were investigated on West Ongul and Teoya Islands, Antarctica, during the wintering period of 16th Japanese Antarctic Research Expedition (1975-1976). The results obtained were as follows: 1) About 150 moss colonies in the region were newly confirmed besides about 150 colonies described previously. Lichen colonies were very sparsely distributed, and all of them occurred on rock faces used by birds as perches. 2) The moss communities which consisted of Bryum pseudo-triquetrum (HEDW.) GAERTH. (this species has been treated as B. inconnexum CARD.) and/or Ceratodon purpureus (HEDW.) BRID, are very abundant to western parts of West Ongul Island. 3) The stands confirming these moss communities are topographically classified into the following 4 types: Stand type I, ground moistened by melt water trickling from snow-drift: Stand type II, ground by snow-drift; Stand type III, periphery ground of snow-drift or snow patch; Stand IV, rock base lying at more upper slope than snow-drift. 4) The moss communities show preference of southwestern to northwestern slopes where they get supply of water from snow-drift melted by solar radiation. departmental bulletin paper